2018
DOI: 10.1177/1521025118773319
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Stressful First Year in College: Could Peer Mentoring Be a Critical Strategy?

Abstract: Peer mentoring has emerged as a viable retention strategy to aid higher education institutions in their efforts to ensure freshmen students make it through that crucial first year and beyond and obtain that degree. Although peer mentoring has been in existence for decades and, there is increasing research on this topic, there are no reviews of the literature more recent than 2009. Utilizing an integrative literature review, the research presented in this article provides an overview of current existing peer me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Typically, peer-mentoring programs involves pairing more experienced students, usually juniors or seniors that serve as mentors for less experienced students usually freshmen or sophomores, for the twofold purpose to promote the educational success of the proté gé and nurture the leadership or counseling skills of the peer mentor. The effectiveness of peer mentoring is supported by cross-institutional research that showed students who participated in such programs displayed higher rates of retention and academic achievement (as measured by grade-point average) than non-participating students with comparable college-entry characteristics (Lane, 2018;Graham & McClain, 2019).…”
Section: Peer Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, peer-mentoring programs involves pairing more experienced students, usually juniors or seniors that serve as mentors for less experienced students usually freshmen or sophomores, for the twofold purpose to promote the educational success of the proté gé and nurture the leadership or counseling skills of the peer mentor. The effectiveness of peer mentoring is supported by cross-institutional research that showed students who participated in such programs displayed higher rates of retention and academic achievement (as measured by grade-point average) than non-participating students with comparable college-entry characteristics (Lane, 2018;Graham & McClain, 2019).…”
Section: Peer Mentoringmentioning
confidence: 99%
“…These timely class discussions and adjustment solution strategies, at or around the time students experience them during their first term of college offers instantaneous relevance and practicality of course information, thus increasing their motivation to attend and put into practice the strategies taught during the FYE course (Reid, Reynolds & Perkins-Auman, 2014;Rogerson, & Poock, 2013). Additionally, these orientation when extended into a full-length course provide abundant opportunities for peer bonding and forum for providing social and emotional support that develops among classmates as they interact frequently in a social context devoted to the student-centered topics of college adjustment and success (Hold & Fifer, 2016;Ang, Lee & Dipolog-Ubanan, 2019;Lane, 2018).These extension and integrated programs is available to administrators to promote awareness and knowledge of campus programs and out-of-class support, increases student use of college resources and services (Barefoot & Fidler, 1996), and useful for early identification and early alert of first-term students that are academically "at-risk" (Klatt & Ray, 2014).…”
Section: First-year Experience Seminars and Extended-orientation Coursesmentioning
confidence: 99%
“…The transition from high school to university is generally described as a demanding and stressful developmental task (e.g., Bruffaerts et al, 2018;Hurst, Baranik, & Daniel, 2013;Lane, 2018). In fact, researchers, practitioners, and administrators commonly assume that 1 st year university students will experience an "academic shock" in which their academic achievement will severely drop compared to high school (Finnie & Martinnello, 2010).…”
Section: Academic Achievement Of 1 St Year Studentsmentioning
confidence: 99%
“…Over the last three decades, a specific line of investigations has focused on the measurement of students' adaptation to tertiary education (Baker & Siryk, 1984;Credé & Niehorster, 2012). Orientation programs, workshops, mentoring, and counseling specifically designed to help 1 st students are manifolds and widespread (e.g., Lane, 2018). Systematic and rather costly interventions such as the First Year Seminars are commonly offered and sometimes universally implemented on campuses across North America (Permzadian & Credé, 2015).…”
Section: Academic Achievement Of 1 St Year Studentsmentioning
confidence: 99%
“…The research on peer mentoring suggests that the practice is an effective retention tool (Crisp and Cruz 2009;Lane 2018). Studies suggest that peer mentoring, when appropriately structured, is effective in creating the right kinds of academic and social support systems to help students make the transition to college which improves retention (Colvin 2015, 224;Cornelius, Wood, and Lai 2016, 202).…”
Section: Introductionmentioning
confidence: 99%